The economics of catfish grow-out culture in freshwater fishpond in Jalaud Sur, Zarraga, Iloilo. - Langreo, Stephen Monares
The study dealt on the economics of catfish grow-out culture in Jalaud Sur, Zarraga. The socio-economic status, production practices and costs and returns of catfish farmers were determined in the study. The researchers selected 27 respondents using purposive sampling., Results of the study showed that catfish farmer have high educational attainment, modern housing facilities, and major alternative sources of income, among others. Moreover, majority (51.85 of the catfish farmers own their ponds. The investment items used by the fish farmers are nets, containers Styrofoam and accessories. Cost and return analysis revealed that variable costs accounted for over 43 of total costs, followed by fixed costs (41.48) and opportunity costs (15.31). Economic indicators were utilized to examine the profitability and viability of catfish culture. Net profit per cropping per farm was P 55,921.59 while financial profit was P 45,678.33. In addition, pure economic profit was P41,897.8. Returns to fixed constant variable cost amounted to P 4.09 and P 3.93, respectively. (p)The major problems encountered by the catfish farmers are diseases and mortality which greatly affect their production. The study recommended that the government together with regional organization like SEAFDEC/AQD should render assistance to the fish farmers through training for scientific fish culture. Private sectors or banks should also provide short-term credit schemes with adequate amounts and low interest. Furthermore, the government should continue its research programs and encourage researchers not only in the biological or technical aspect of catfish culture but in economics as well.